Efeitos da aclimatação térmica no metabolismo aeróbico, parâmetros cardiovasculares e tolerância térmica em girinos de Bokermannohyla ibitiguara - Longhini, Leonardo Sambini (Universidade Federal de São Carlos, 2020)
Thermal acclimation is suggested to provide a reversible physiological adjustment in response to environmental changes, conferring resilience in a climate change scenario. Since amphibians may be more vulnerable to habitat modification because of their life cycle dependence on both land and water, it is critical to identify species’ ability to acclimate in warming climates. Here, we investigate the effects of temperature acclimation on tadpoles of a stream-breeding savanna tree frog (Bokermannohyla ibitiguara) and the relationship between the thermal conditions experienced in their microhabitat. We quantified variation in thermal physiology by measuring routine and maximum metabolic rate (RMR and MMR, respectively) at different test (15, 20, 25, 30 e 34°C) and acclimation temperatures (18 and 25°C). In addition, we measured body characteristics of the two groups and the heart rate (fH) before and after autonomic blockade with atropine and sotalol. Further, we determined the critical thermal maximum (CTmax) and warming tolerance (WT=CTmax-Tmax), which were not affected by acclimation. The routine and maximum metabolic rate and fH increased with acute exposure to high test temperatures, although the acclimation did not affect significantly the maximum metabolic rate, fH or the autonomic tones. In addition to this absence of physiological compensation, we observed a decrease in aerobic scope in the group acclimated to 25 °C, followed by a 53.8% reduction in body mass in the tadpoles of this group. In conclusion, the tadpoles of B. ibitiguara inhabit in a thermally stable environment and are not able to thermally acclimate to high temperatures like 5°C above those found in their micro-habitat, making the species more vulnerable to climate changes or/and with degradation of their habitat.
Effects of thermal acclimation on aerobic metabolism, cardiovascular parameters and thermal tolerance in tadpoles of Bokermannohyla ibitiguara
Keywords: Mudanças climáticas; Frequência cardíaca; Tônus autonômico; Consumo de oxigênio; CTmax; Climate change; Heart rate; Autonomic tonus; Oxygen consumption; CIENCIAS BIOLOGICAS::FISIOLOGIA; CIENCIAS BIOLOGICAS::FISIOLOGIA::FISIOLOGIA COMPARADA